Compression apparel effects on soft tissue vibrations - Coza, A.; Nigg, B. M. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Compression apparel has been reported to have positive effects on performance (Kraemer et al., 1998). Mechanisms to explain the improved performance included change in kinematics, change in blood flow and the damping of soft tissue vibrations. Soft tissue vibrations are important for the energetics of running (Nigg and Wakeling, 2001) since muscle activity is required to damp these vibrations (Boyer and Nigg, 2006). Consequently, damping the soft tissue vibrations through apparel should decrease the muscle activity and, therefore, decrease the needed energy. However, the effect of compression apparel on vibration damping and muscle activity has never been quantified. The goal of this study was to quantify the effects of compression apparel on (a) the damping of soft tissue vibration and (b) muscle activity during treadmill running.